Users’ perceptions on security of mobile computing for adoption of e-applications in South Africa - Mapande, Fhatuwani Vivian (My University, 2018)
The advancement of technology, particularly in the area of mobile computing, revolutionizes the way business is done in many industries such as the education sector, government sector, financial institutions, retail sector and the way people conduct their daily activities. The current technology provides influential tools for organisations and can significantly influence their operation, structure and approach. The development of mobile computing has created a new innovation for various industries by increasing the availability, frequency and speed of communication between the organisations and the individuals. However, users’ perceptions can play an important role towards the adoption of these new developments. The overriding purpose of this study was to investigate the users’ perceptions on the security of mobile computing in South Africa for adoption of e-applications. The literature review was concentrated on the process of progressive development occurring during the study. To accomplish that goal it became necessary to reach some essential objectives i.e. investigating the users’ perceptions models in literature. For the purpose of the study, it was important to propose a research framework for users’ perceptions on the security of mobile computing with the potential for the adoption of e-applications in South Africa. The research evaluated the proposed framework to establish if there is any relationship between the e-application adoption factors. Furthermore, the hypotheses were tested to determine which factors would influence the adoption of e-applications in South Africa. Technology Adoption Model 2 (TAM2) and Diffusion of Innovation (DOI) provide the theoretical basis for explaining how users perceive e-application services that they access and operate through mobile computing. To achieve that, a quantitative study was conducted with South African residents, with respect to mobile security perceptions; 476 valid questionnaires were received from the participants who were selected non-randomly. Questionnaires were developed from the proposed research framework derived from DOI and TAM2 and the items were adopted from other prior technology adoption studies. Through the use of the survey instrument developed for this study, data were collected in order to address the importance of this study based on the problem statement posed in the first chapter of this dissertation. The valid questionnaires were analysed by using the Statistical Package for the Social Sciences (SPSS), Version 24.0. Reliability analysis, principal component analysis, correlations and multiple linear regression tests were conducted. Among other things this study made sure that ethical considerations are adhered to. The findings revealed positive relationships between perceived usefulness of security mechanisms, perceived ease of use of security mechanisms, subjective norm on security mechanisms, relative advantage of security mechanisms, compatibility of security mechanisms, complexity of security mechanisms, aesthetics of security mechanisms interface and intention to adopt e-applications. Furthermore, subjective norm on security mechanisms was strongly correlated to intention to adopt e-applications, complexity of security mechanisms strongly correlated to perceived usefulness of security mechanisms, relative advantage of security mechanisms and aesthetic of security mechanisms interface strongly correlated to perceived usefulness of security mechanisms. In addition, subjective norm of security mechanisms strongly influence intention to adopt eapplications in South Africa. Also, aesthetics of security mechanisms interface strongly influence both perceived usefulness of security mechanisms and perceived ease of use of security mechanisms. The reason behind it may be interpreted as users nowadays seeing the beauty as the platform to attract and encourage them to use e-applications. Finally, the proposed model analysis and survey evaluation will enable South African organizations to make informed decisions about the use of e-applications services. These findings contribute to a road map for the education sector, government sector, financial institutions, and retail sector as well as to encourage their customers or clients to adopt e-applications.
M.Tech (Department of Information technology, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: Adoption, security mechanism, e-applications, Diffusion of Innovation (DOI), Technology Adoption Model 2(TAM), Perceptions, Mobile computing; Mobile computing -- Security measures.; Mobile computing -- Social aspects.; Electronics -- South Africa.